Registered Cartels in Austria. An Overview - Nikolaus Fink; Philipp Schmidt-Dengler; Konrad Stahl; Christine Zulehner (Austrian Institute of Economic Research (WIFO), 2015)
Cartels were legal to a large extent in Austria until the country's EU accession in 1995. We examine archival material on registered horizontal cartels to learn about their inner working. Applying content analysis to legally binding cartel contracts, we comprehensively document different collusion methods along the lines described by Stigler (1964). Quota cartels employ regular reporting schemes and use compensation mechanisms for departures from set quotas. Specialisation cartels divide markets and rely the least on information exchange and punishment. Price and payment condition cartels primarily aim to prevent secret price cuts, requiring information provision upon request, allow for discretionary decision-taking and (sometimes immediate) punishment. These stylised facts on the contractual arrangements suggest that the possibility to write legally binding agreements was employed to address the usual obstacles to sustaining collusion.
Keywords: 330; Collusion; Cartels; Legal Cartels; Contracts